The evolution of Indonesia’s military doctrines in Old Order, New Order and Reformation Era - Hananto, Kus; Sity Daud, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the evolution of the Indonesian military doctrines during the Old Order, the New Order, and the Reformation Era. Under Sukarno’s leadership, the use of military force was outward looking and offensive, apart from constantly viewing neighbouring countries as potential enemies. Suharto prioritised homeland security and built synergies among nations within the region. The military doctrine during the Reformation Era has undergone four amendments as an effort to improve military professionalism. This study analyses factors that led to the evolution of the Indonesian military doctrine and explains the evolution that took place during the three periods. This study employed a qualitative method supported by Neoclassical Realism analysis through literature study, document analysis, and interviews as an attempt to analyse various factors for the military doctrine evolution. The study outcomes showed that domestic politics emerged as the most dominant factor that sparked the evolution of military doctrine. Finally, this study concludes that the evolutionary doctrine of the Indonesian military reflects a form of adjustment to political developments and strategic environment in maintaining the Indonesian national security.